Towards a theory of denominals : a look at incorporation, phrasal spell-out and spanning - Bleotu, Adina Camelia (Empirical approaches to linguistic theory, 2019)
"In Towards a Theory of Denominals, Adina Camelia Bleotu takes a comparative look at denominal verbs in English and Romanian from various theoretical frameworks such as lexical decomposition, distributed morphology, nanosyntax and spanning. The book proposes a novel spanning analysis, arguing for its explanatory superiority to incorporation/conflation or nanosyntax in accounting for the formation and behaviour of denominals. It provides useful empirical insights, drawing from rich data from English discussed widely in the relevant literature, but also presenting novel data from Romanian not explored in detail before. Many interesting theoretical issues are also discussed, such as the (lack of) correlation between the (un)boundedness of the nominal root and the (a)telicity of the resulting verb, the verb/ satellite-framed distinction and others"--